SOSIALISASI PARENTING PENDIDIKAN SEKS BAGI ORANG TUA ANAK BERKEBUTUHAN KHUSUS DI SLB NEGERI I KOTA PARE PARE SULAWESI SELATAN - Meidina, Tatiana; Bastiana, Bastiana; Kasmawati, St; Sulasminah, Dwiyatmi; Ariastuti, Wizerti (Transpublika Publisher, 2023)
The objective of this community service activity is to conduct a comprehensive study aimed at enhancing the understanding of parents with children with special needs at SLB Negeri 1 Pare-Pare City, South Sulawesi. The study specifically focuses on the challenges faced by parents in comprehending the changes in their children with special needs during the transition from childhood to adolescence. The behavior and needs of children with special needs during adolescence are similar to those of children without special needs. Almost all children with special needs do not encounter issues with their body growth and development, including when they enter puberty. One of the responsibilities of parents is to provide an understanding of sex, along with guidance on how to protect themselves from sexual harassment and violence. To encourage parents of children with special needs to assist their children in understanding these issues, socialization is conducted along with simple exercises in parenting sex education for parents of children with special needs. The method used involves lectures and question-and-answer sessions on simple sex parenting exercises, with 22 parents participating. The results obtained after this activity show an increase in sexual parenting knowledge, as evidenced by the pre-test and post-test results. There was an 85.7% increase in the knowledge of the training participants, with a noticeable average improvement. This suggests that it may be recommended to expand the scope of service material with more complex exercises.